2016
DOI: 10.1111/gfl.12167
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term chemical evolution and modification of continental basement brines – a field study from the Schwarzwald, SW Germany

Abstract: Highly saline, deep‐seated basement brines are of major importance for ore‐forming processes, but their genesis is controversial. Based on studies of fluid inclusions from hydrothermal veins of various ages, we reconstruct the temporal evolution of continental basement fluids from the Variscan Schwarzwald (Germany). During the Carboniferous (vein type i), quartz–tourmaline veins precipitated from low‐salinity (<4.5wt% NaCl + CaCl2), high‐temperature (≤390°C) H2O‐NaCl‐(CO2‐CH4) fluids with Cl/Br mass ratios = 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 59 publications
3
33
1
Order By: Relevance
“…A notable exceptions are recent studies on the Freiberg district (Bauer et al 2019;Ostendorf et al 2019), where Sm-Nd geochronology and fluid inclusion analyses have illustrated that fluoritebarite mineralization is of Mesozoic age and related to the migration and mixing of shallow crustal, highly saline brines. This mineralization style is very similar to many other fluorite-barite veins known from Variscan basement exposures in Europe, with examples from Germany, France, Spain, Poland, Czech Republic, and Great Britain (Boiron et al 2010;Kraemer et al 2019;Muchez et al 2005;Walter et al 2016). The formation of this vein-style mineralization is typically related to the opening of the northern Atlantic in the Cretaceous (Walter et al 2018b) and that share fluid inclusion systematics (e.g., (Baatartsogt et al 2007;Walter et al 2017)).…”
Section: Introductionsupporting
confidence: 74%
“…A notable exceptions are recent studies on the Freiberg district (Bauer et al 2019;Ostendorf et al 2019), where Sm-Nd geochronology and fluid inclusion analyses have illustrated that fluoritebarite mineralization is of Mesozoic age and related to the migration and mixing of shallow crustal, highly saline brines. This mineralization style is very similar to many other fluorite-barite veins known from Variscan basement exposures in Europe, with examples from Germany, France, Spain, Poland, Czech Republic, and Great Britain (Boiron et al 2010;Kraemer et al 2019;Muchez et al 2005;Walter et al 2016). The formation of this vein-style mineralization is typically related to the opening of the northern Atlantic in the Cretaceous (Walter et al 2018b) and that share fluid inclusion systematics (e.g., (Baatartsogt et al 2007;Walter et al 2017)).…”
Section: Introductionsupporting
confidence: 74%
“…The replacement of anhydrous minerals (dolomite, feldspars, and plagioclases) by hydrated minerals (talc and chlorite) increases the chlorinity during the alteration of the crystalline basement by fluids. This process has already been suggested in unconformity U-type deposits hosted in the Athabasca Basin in Canada [52,53], in the Modum Complex in Norway [39], and in the Schwarzwald district in Germany [54,55].…”
Section: Discussionmentioning
confidence: 61%
“…t1 ≠ t2 represents the fact that the circulation of the brines derived from the seawater evaporation and derived from the serpentinization should have been temporally disconnected in the deposit. 13 Geofluids ones ( [39,52,54,55,58,80]; Hovland et al, 2018). Carrying this idea a step further, Scribano et al [81] suggested that the formation of a certain subseafloor giant salt deposit in deep marine basins may be genetically related to the serpentinization of ultramafic rocks.…”
Section: What About the Regional Circulation Of Primary Brines?mentioning
confidence: 99%
“…T h and Tm ice ranges, and the occurrence of CaCl 2 in the fluid) are similar to those of the fluid inclusions trapped in ore and gangue minerals in post-Variscan (i.e. Jurassic-Cretaceous) F-Ba-(Pb-Zn-Ag) deposits in Sardinia and Central-Western Europe (Bauer et al, 2019;Behr et al, 1987;Boni et al, 2002Boni et al, , 2009Cathelineau et al, 2012;Muchez et al 2005;Munoz et al, 1994;Walter et al, 2016). In particular, among the similarities between the Montevecchio and the Saint Salvy deposit (specifically for the zinciferous M4 stage, Munoz et al, 1994) Salvy (Munoz et al, 1994).…”
Section: General Contextmentioning
confidence: 63%